The meaning of participative implementation processes for local energy balancing in a systemic approach. (August 2021) - Knemeyer, Ann-Katrin; Ehrenstein, Ulrike; Becker, Daniela; Hildebrand, Jan; Schweizer-Ries, Petra
Abstract: Within an interdisciplinary, participatory and transformative research approach, a multi-method research design was used to examine acceptance criteria of energy balancing technologies. Energy balancing is important to integrate the increasing amount of renewable energies efficiently into the energy supply system: due to the fluctuating power production from wind and solar power plants flexibilities are needed. The study applied a holistic, systemic perspective, not only focused on the technologies, but also on consumers, producers and the interwining of both. Within the study, a mixture of balancing technologies, suitable for decentralized energy systems on a regional or local level, took center stage. The most relevant stakeholders to define acceptable pathways for planning and realization processes for decentralized energy balancing concepts are in the focus of interest. They are identified as decision holders to foster the implementation of energy balancing. For environmental planning, regional participation and related governance processes results state a lack of awareness for the necessity of energy balancing. A shared understanding of future energy balancing needs and possibilities within respective regarded areas is crucial besides administrative boundaries of e.g. municipalities. Furthermore, different levels to integrate municipal stakeholders and citizens in an adapted planning process for energy balancing concepts have been identified and a prototype of a strategic planning tool was developed and tested. Highlights: Energy balancing is important to integrate increasing amounts of renewable energy. There is a lack of awareness for the necessity of energy balancing. Energy balancing enables stakeholder to participate actively in energy transition. The complexity of energy balancing concepts hampers regional planning processes.